PENINGKATAN HASIL BELAJAR DAN MOTIVASI SISWA SMP PADA MATERI KALOR MELALUI MODEL PEMBELAJARAN INKUIRI TERSTRUKTUR - Harun, Naura Maheshi; Nurita, Tutut (PENSA E-JURNAL: PENDIDIKAN SAINS, 2024)
This study aims to describe the improvement of knowledge learning outcomes and motivation of junior high school students after implementing a structured inquiry learning model on heat material. The subjects used in this study were students of class VII C in one of the junior high schools in Surabaya. The type of research used is quantitative research with pre-experiment method with One Group Pretest-Posttest Design. The data collection techniques used were written test, questionnaire, and observation. The data obtained were analyzed to determine whether or not there was an increase in knowledge learning outcomes and student motivation after being given learning with a structured inquiry model. The results of this study showed that 7 students received a high category of improvement in knowledge learning outcomes and 23 students received a moderate improvement category. This indicates that all students in class VII C experienced an overall increase in knowledge learning outcomes with each category measured by N-Gain analysis. Student learning motivation using ARCS aspects as a whole showed positive results in the excellent category. Based on these results, it can be concluded that the application of structured inquiry learning model can improve the learning outcomes of knowledge and motivation of junior high school students on heat material. Keywords: Structured Inquiry, Learning Outcomes, Motivation, Heat.